STUDI PROVENANCE BATUPASIR FORMASI - FORMASI DI CEKUNGAN OMBILIN, SUMATRA BARAT - -, Euis Tintin Yuningsih (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
Based on rock composition percentage of feldspar, quartz and rock fragment on Q-F-L triangle diagram, the sandstone provenance of Brani Formation is continental block, otherwise Sawahlunto and Sawahtambang Formations is recycled orogen. Qm-F-L triangle diagram shows the provenance of Brani, Sawahlunto and Sawahtambang Formations is continental block, Sangkarewang and Ombilin Formations is transitional magmatic arc placed in the Cretaceous orogen belt as a result of convergency of Mergui-Woyla microplates. Based on rock composition percentage on the Qp-Lv-Ls triangle diagram, the source for Brani and Sawahtambang Formations is mixed orogenic sand, Sawahlunto Formation is collision orogen and mixed orogenic sand, otherwise the source for Sangkarewang and Ombilin Formations is arc orogen where the zone of collision is the suturing of Mergui-Woyla microplates, Qm-P-K triangle diagram shows that Brani, Sawahlunto and Sawahtambang Formations have high maturity or stability from continental block indicated the source of stable micro continen (continental block provenances) as a part of Mergui-Woyla terrane, Sangkarewang Formation has low maturity or stability